Subluxation of lens alarms to homocystinuria - Patel, Abhishek Mansinh; Sheikh, Khushnood M.; Shastri, Manisha B. (International Journal of Research in Medical Sciences, 2016)
Homocystinuria is a disorder of methionine metabolism. The term Homocystinuria refers as abnormally large amounts of homocystine are excreted in the urine. The condition was caused by impaired functioning of the cystionin B-synthetase (CBS) enzyme. Homocystinuria is an autosomal recessively inherited defect in the trans-sulfuration pathway (homocystinuria I) or methylation pathway (homocystinuria II and III). The most common form of homocystinuria is characterized by near sightedness, dislocation of the lens at the front of the eye, an increased risk of abnormal blood clotting, and brittle bones that are prone to fracture or other skeletal abnormalities. Some affected individuals also have developmental delay and learning problems. Homocystinuria has a current cumulative detection rate of 1 in 344,000. A high concentration of homocysteine makes fibrillin unstable. Fibrillin is responsible to form the structures which hold the lens of the eye in place. We report a case of 28 year old male with unilateral Subluxation of lens following trauma coincidentally diagnosed to have Homocystinuria and bilateral Subluxation of lens. On account of case we would like to emphasize homocystinuria should be considered as differential diagnosis in Subluxation of lens.